Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12864-019-6042-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic informed by transcriptomic for salivary glands components of the camel tick Hyalomma dromedarii

Abstract: Background The hard tick Hyalomma dromedarii is one of the most injurious ectoparasites affecting camels and apparently best adapted to deserts. As long-term blood feeders, ticks are threatened by host defense system compounds that can cause them to be rejected and, ultimately, to die. However, their saliva contains a cocktail of bioactive molecules that enables them to succeed in taking their blood meal. A recent sialotranscriptomic study uncovered the complexity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 80 publications
1
32
2
Order By: Relevance
“…After PFAM filtering, 15,342 contigs were annotated of which 1,749 was classified as secretory. The transcriptome study was followed up with proteomic analysis of SGE from ticks collected in the field (Bensaoud et al, 2019a , b ). Fractionation of SGE was performed using 1D-SDS-PAGE, after which bands were cut-out, tryptic digested and analyzed using LC-MS/MS.…”
Section: Complexity Measured By Next-generation Sequencing Of Transcrmentioning
confidence: 99%
“…After PFAM filtering, 15,342 contigs were annotated of which 1,749 was classified as secretory. The transcriptome study was followed up with proteomic analysis of SGE from ticks collected in the field (Bensaoud et al, 2019a , b ). Fractionation of SGE was performed using 1D-SDS-PAGE, after which bands were cut-out, tryptic digested and analyzed using LC-MS/MS.…”
Section: Complexity Measured By Next-generation Sequencing Of Transcrmentioning
confidence: 99%
“…Regarding the combined timepoint profiles of expression of transcripts encoding these proteins in males and females of R. zambeziensis, they were also similar to those seen in R. microplus adults with the exception again of metalloproteases, but also of evasins, 8.9 kDa protein family and mucins, where females presented greater representation of these transcripts than males. We have already pointed out above the possible explanation for the discrepancy between levels of expression of IGBP in the sialotranscriptome generated in the present study and in that of males of the two-or three-host tick H. dromedarii that can infest cattle as well as camelids 40,41 . At present it is not possible to ascribe a role for secreted salivary protein families in determining the number of hosts different species of ticks have in their life cycles.…”
Section: Comparisons Between the Sialotranscriptomes Of Males And Femmentioning
confidence: 52%
“…The exception is Hyalomma dromedarii 40 , where transcripts for IGBPs were not found in the salivary gland transcriptomes from males and females feeding on camels and a partial sequence was obtained for a single type of IGBP in the corresponding proteome. Camelids of the Saharan regions are the natural hosts of H. dromedarii 41 , mammals which produce mainly single chain antibodies, instead of conventional antibodies. Towards understanding why males of this species do not produce an array of IGBPs it will be interesting to examine if IGBPs from other species of ticks bind to single chain antibodies from camelids.…”
Section: Representation Of Specific Protein Families In the Context Omentioning
confidence: 99%
“…This molecular weight suggested that it belongs to protease inhibitor proteins of the type serpin which are one of the most important serine protease inhibitors that ticks rely on to control host hemostasis and immunity [34]. Seven significantly overexpressed serpins were identified in the salivary gland transcriptome of partially fed H. dromedarii females, from which only five proteins were identified in the proteomic analysis [35] [36]. Identification of these serine protease inhibitors from salivary glands of the semi-fed females suggests their crucial role in tick blood feeding success.…”
Section: Discussionmentioning
confidence: 99%